Penerapan Teknik Perawatan Payudara (Breast Care) terhadap Produksi ASI di Ruang Cempaka RSUD Dr. Soehadi Prijonegoro Sragen - Riska Utami; Anjar Nurrohmah; Neny Utami (STIKES Columbia Asia Medan, 2024)
Background : Breast milk is a substance produced by the body naturally by the breast glands. Breast milk is an emulsion of fat in a solution of protein, lactose, and organic salts, white blood cells secreted by the breast glands so that breast milk is the perfect food for growth and development and immunity of the baby. Breast milk production that is small or not smooth can interfere with exclusive breastfeeding, so efforts are needed to increase breast milk production by treating non-pharmacological techniques, one of which is breast care. Breast care is an action in maintaining the health and cleanliness of the mother's breasts, flexing and strengthening the nipples to stimulate the body to secrete lactogen and prolactin hormones, improve blood circulation, prevent obstruction of milk release so that breast milk production increases. Objective: to determine the results of the implementation of breast care techniques on breast milk production of postpartum women in the Cempaka Room of RSUD dr. Soehadi Prijonegoro Sragen. Method: This research is a case study research conducted on 2 postpartum mother respondents by doing breast care for 2 days with a frequency of 2 times a day for 30 minutes. Results: From the results of observations on both respondents there was a development of breast milk production from before and after breast care from the first and second days experienced a significant increase. Conclusion: There is an increase in breast milk production and before and after breast care from not smooth to smooth.